The impact of empowerment of women leaders on job performance: An empirical study on government sector in KSA - Sharawi, Hossam Hassan; Al-Said, Amani Saleh (Journal of Economic, Administrative and Legal Sciences, 2024)
The current study investigates the impact of managerial empowerment on the job performance of female leaders in the government sector in the Kingdom of Saudi Arabia in 2023. It relies on an empirical study that included a sample of 70 male and female leaders from one of the government sectors during the second quarter of 2023. The study found a positive and significant impact of effective communication, as one of the dimensions of managerial empowerment, on the job performance of female leaders in this sector. The study’s results also show insignificant impact of other dimensions of managerial empowerment on female leadership, namely: authority delegation, training, motivation, and teamwork, despite the fact that the results of simple linear regression analysis indicate that these dimensions have a positive and significant impact. This study is considered the first study, to the researcher’s knowledge, to be applied to female leaders in the government sector in the Kingdom of Saudi Arabia.